Investigation of Angiogenic Mechanisms Involved in Omentum Transplantation - Xiang, William (My University, 2017)
The omentum is an intra-abdominal fat pad. It is a well-vascularized structure that is sometimes referred to as the "policeman of the abdomen" for its proclivity to adhere to sites of intra-abdominal inflammation or injury. It is also recognized for the ability to provide effective tissue reinforcement and bring a source of vascular supply to areas of inflammation and healing. In clinical practice, the omentum is often used to buttress surgical repair - and to ensure adequate vascularization of healing tissues. A limitation in its use is that many times the mobility of the omentum is constrained because it is time-consuming and not always feasible. Thus, this project addressed the question of whether the omentum can be used as a free, autonomous graft by (1) determining that a free omental graft remains viable, and (2) characterizing the neo-vascularization of the recipient bed.